Aplicación de las tic como herramienta metodológica en el proceso de enseñanza-aprendizaje en los estudiantes del segundo bachillerato de informática de la Unidad Educativa Jaime Roldos Aguilera periodo lectivo 2021-2022 - Bravo Sanchez, Jamileth Stephania (2022)
The research work tries to know the application of ICT as a methodological tool in the teaching-learning process in the students of the Second High School of Computer Science of the "Jaime Roldós Aguilera" Educational Unit. To do this, it is first necessary to know the so-called Tics, since when we refer to them we are not only talking about technology, but also about the resources that can be used thanks to said technology. This research focuses on information and communication technology as an educational tool that promotes purposeful learning. To achieve this, 15 students of 2nd Baccalaureate "Informatics" were taken as a reference population, resulting in a total population of 30. The necessary statistical tests were carried out, using the survey technique as a questionnaire as a data collection instrument. This survey consists of 10 questions addressed to 15 students, all with the purpose of verifying the relevance of the application of ICTs as a methodological tool and analyzing the level of knowledge of teachers and students about their use. Once the survey was carried out, the analysis was made that more than 50% of the students surveyed know what ICTs are, which makes their inclusion within the teaching-learning process more feasible.